The THE PRACTICE OF DHIKR BEFORE SLEEP AND ITS IMPACT ON SLEEP CHARACTERISTICS IN THE ELDERLY OF JEMBER REGENCY - Aulya Anharini; Zahreni Hamzah; Ahmad Nafi; Azham Purwandhono; Kristianningrum Dian Sofiana; Moh. Sholeh (International Islamic Medicine Forum, 2026)
Dhikr provides a relaxing effect that contributes to improved sleep quality by reducing cortisol and regulating sleep hormones. This study analyzed differences in sleep characteristics between elderly people who performed dhikr before bed and those who did not in a cross-sectional study of 67 respondents. The results showed significant differences (p < 0.05), where elderly people who performed dhikr had better sleep quality, faster latency, higher duration and efficiency, and fewer sleep disturbances. Thus, dhikr is effective in improving sleep characteristics in the elderly.